Penerapan Standar Operasional Prosedur Pelayanan Food & Beverage Service di Express Restaurant - Dwi Hanadya; Nyayu Ully Auliana; Muhammad Andriansyah (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
Standard operating procedures (SOPs) are very important to set work standards so as not to fall out of the standard rules. In the world of tourism, SOPs in hospitality are used to discipline employees so that every work done cannot be separated from the standards set. This research was conducted at Amaris Hotel Palembang, a two-star hotel that has restaurant facilities, ballrooms, hotel rooms, etc. In this study using observation methods, or discovery research that will examine how SOPs in the food and baverage section are implemented at Amaris Hotel. This research study found that every employee who works in the food and beverage section has fulfilled SOPs when working, even before work they have prepared SOP prefixes before employees go to restaurants. This is a priority to ensure that all work carried out is in accordance with SOPs and maintain food and beverage hygiene for hotel guests.